2018
DOI: 10.3389/fimmu.2018.02099
|View full text |Cite
|
Sign up to set email alerts
|

Herpesviruses and MicroRNAs: New Pathogenesis Factors in Oral Infection and Disease?

Abstract: The oral cavity incessantly encounters a plethora of microorganisms. Effective and efficient oral innate and adaptive immune responses are incumbent to maintain healthy mucosa. A higher prevalence of Human Herpesviruses (HHV), a family of large enveloped DNA viruses, has been reported in multiple oral inflammatory diseases suggesting their involvement in disease progression. However, the viral components contributing to oral disease remain obscure. MicroRNAs (miRNA) are non-protein coding, single stranded ribo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 175 publications
0
35
0
Order By: Relevance
“…The viral glycoprotein B downregulates the expression of HLA-DR molecules at the plasma membrane of infected cells by diverting these molecules into the exosomes (Temme et al, 2010). Furthermore, EVs from HSV-1 infected cells have viral miRNAs, which are involved in latency regulation (Naqvi et al, 2018). Han et al found that viral miRNAs like miR-H28 and miR-H29 are encapsulated into EVs from the HSV-1 infected cells.…”
Section: Herpes Simplex Virus 1 (Hsv-1)mentioning
confidence: 99%
“…The viral glycoprotein B downregulates the expression of HLA-DR molecules at the plasma membrane of infected cells by diverting these molecules into the exosomes (Temme et al, 2010). Furthermore, EVs from HSV-1 infected cells have viral miRNAs, which are involved in latency regulation (Naqvi et al, 2018). Han et al found that viral miRNAs like miR-H28 and miR-H29 are encapsulated into EVs from the HSV-1 infected cells.…”
Section: Herpes Simplex Virus 1 (Hsv-1)mentioning
confidence: 99%
“…The highly complex HSV-1 genome encodes several mature miRNA sequences [ 164 ]. These HSV-1 derived miRNAs are thought to be involved in repressing the expression of target genes critical for the regulation of viral latency [ 164 , 165 ].…”
Section: Evs In Viral Infections Affecting the Nervous Systemmentioning
confidence: 99%
“…The highly complex HSV-1 genome encodes several mature miRNA sequences [ 164 ]. These HSV-1 derived miRNAs are thought to be involved in repressing the expression of target genes critical for the regulation of viral latency [ 164 , 165 ]. Interestingly, EVs from HSV-1 infected cells have also been shown to contain both viral mRNA and miRNA such as miR-H28 and miR-H29 [ 51 , 166 ].…”
Section: Evs In Viral Infections Affecting the Nervous Systemmentioning
confidence: 99%
“…Although viruses are also present within the oral cavity with differences observed between health and disease states, there is limited knowledge about their relationship to periodontal disease 20 . Studies suggest that viruses, including herpes simplex virus-1,2, Epstein-Barr virus, and cytomegalovirus play important roles in periodontal disease [21][22][23][24][25][26][27][28][29] . Also, in recent studies, other different viruses have been associated with periodontal disease, however, a comprehensive evaluation of the oral virome in relationship to periodontal disease using shotgun sequencing has not been carried out in mice and to a limited extent in humans [30][31][32][33] .…”
Section: Introductionmentioning
confidence: 99%